HEALING of LARGE PERIAPICAL LESION FOLLOWING CONVENTIONAL ROOT CANAL TREATMENT- A CASE REPORT - Demet Altunbaş; Recai Zan; Fatma Kaya; Kerem Engin Akpınar (Cumhuriyet University, 2020)
The infected pulp, microorganisms toxins, metabolic products, chemical agents, mechanical irritations, foreign substances, trauma and host defense plays a role in the periapical tissue diseases. Options for the treatment of large periapical lesions range from non-surgical root canal treatment and/or apical surgery to extraction. Although apical surgery may be a treatment option in these cases, conventional root canal treatment should be the first choice. The aim of this case report is to report that the large size of a periapical lesion does not always need a surgical approach and even large periapical lesions heal following a conservative endodontic therapy.